2008
DOI: 10.1128/jvi.00401-08
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mucosal Immunoglobulin A Response and Solid Protection against Foot-and-Mouth Disease Virus Challenge Induced by a Novel Dendrimeric Peptide

Abstract: The successful use of a dendrimeric peptide to protect pigs against challenge with foot-and-mouth disease virus (FMDV), which causes the most devastating animal disease worldwide, is described. Animals were immunized intramuscularly with a peptide containing one copy of a FMDV T-cell epitope and branching out into four copies of a B-cell epitope. The four immunized pigs did not develop significant clinical signs upon FMDV challenge, neither systemic nor mucosal FMDV replication, nor was its transmission to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 59 publications
6
101
1
1
Order By: Relevance
“…A general problem with most subunit vaccines is that they do not elicit a protective immune response comparable with that induced by live virus or killed whole-virus vaccines (66). Peptide vaccines based on the G-H loop (70) do not appear to fully mimic the conformation of the native B-cell epitopes and stimulate antibody of rather narrow specificity, which appears to be T-D (19,25,42). In contrast, studies of responses to traditional FMDV vaccines, which utilize intact inactivated virus, have shown that they stimulate rapid antibody responses that can provide protection against disease within 4 to 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…A general problem with most subunit vaccines is that they do not elicit a protective immune response comparable with that induced by live virus or killed whole-virus vaccines (66). Peptide vaccines based on the G-H loop (70) do not appear to fully mimic the conformation of the native B-cell epitopes and stimulate antibody of rather narrow specificity, which appears to be T-D (19,25,42). In contrast, studies of responses to traditional FMDV vaccines, which utilize intact inactivated virus, have shown that they stimulate rapid antibody responses that can provide protection against disease within 4 to 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of specific IgA responses was detected in serum from the animals showing a higher neutralizing response (pigs 4 and 8). Several studies associate the induction of specific IgA with protection and suggest that vaccines that induce local IgA responses may be more effective (18,22,26). Moreover, mutant transcripts were able to induce a specific T-cell response in four out of the eight animals inoculated.…”
Section: Discussionmentioning
confidence: 99%
“…upper mucosae has been correlated with protection in infected and vaccinated pigs (18,22,26). ELISA titers of Ͼ2 (corresponding to a 1:50 dilution of serum) were detected for both animals.…”
Section: O1k-⌬sl1(vp3-h 56 ) Rna Is Attenuated In Swinementioning
confidence: 97%
“…This is a combination of polymer-lipid containing doxycycline which could have application in the treatment of intracellular infections that are primarily resident in the spleen like brucellosis, ehrlichiosis, etc. A number of studies are reported on horses infected with babesiosis, Streptococcus equi, T. gondii and Strongylus vulgaris infections using liposomes [ 254 ], polymeric nanospheres [ 255 ], dendrimers [ 256 ] and micelles [ 257 ] respectively. A recent study revealed the improved therapy of theileiriosis in cattle with solid lipid nanoparticles (SLN) of buparvaquone [ 258 ].…”
Section: Veterinary Applications Of Targeted Drug Delivery Systemsmentioning
confidence: 99%